2015
DOI: 10.1177/0886260515596335
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Victimization of Violence Committed by Relatives With Psychiatric Disorders

Abstract: Persons with psychiatric disorders are at an increased risk of committing violence, with approximately half of all violence being perpetrated against family members. However, family violence perpetrated by persons with psychiatric disorders is a highly under-researched area, so much so that it is impossible to even approximately estimate the extent of the problem. This article presents the results of a national online survey of 573 adults with an adult relative with psychiatric disorders. Nearly half (47%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
5
26
1
Order By: Relevance
“…Reports of patient violence do not necessarily reduce or disappear following first onset and treatment commencement (Milton et al ., ; Steinert, Wiebe, & Gebhardt, ). Further, contrary to prevailing myths and misconceptions and in line with other reports of domestic violence, patient‐initiated violence in psychosis is more frequently directed towards people already known to them such as family members (rather than strangers) and who may be co‐resident and female (typically mothers) (Belli et al ., ; Fawzi, Fawzi, & Fouad, ; Labrum & Solomon, ; Nielssen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of patient violence do not necessarily reduce or disappear following first onset and treatment commencement (Milton et al ., ; Steinert, Wiebe, & Gebhardt, ). Further, contrary to prevailing myths and misconceptions and in line with other reports of domestic violence, patient‐initiated violence in psychosis is more frequently directed towards people already known to them such as family members (rather than strangers) and who may be co‐resident and female (typically mothers) (Belli et al ., ; Fawzi, Fawzi, & Fouad, ; Labrum & Solomon, ; Nielssen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be particularly true for mothers, who are considered to be the most affected by this type of violence (Nordström and Kullgren, 2003; Estroff et al., 1994). It has been suggested that this increased risk of violence experienced by mothers may be related to the proximity they share with their child in comparison to other family members (Estroff et al., 1998; Labrum and Solomon, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most individuals with severe mental illness are cared for by their family (Copeland and Heilemann, 2008;Lefley, 2009;Onwumere et al, 2014) and this is no different for people with a forensic psychiatric history (Nordstro¨m et al, 2006). As per Rowaert et al (2016), the family is considered to be the primary source of support for people with a forensic psychiatric history, despite the fact that families who live and care for a severely mentally ill relative carry a heavy burden (Maurin and Boyd, 1990;Provencher et al, 2003;Saunders, 2003) and often face violence (Labrum and Solomon, 2017;McCann et al, 1996;Nordstro¨m et al, 2006). Nearly half of individuals caring for family members with forensic psychiatric histories report being victims of violence (Chan, 2008;Estroff et al, 1994;Labrum and Solomon, 2017;Solomon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Physical violence, according to literature on intimate partner violence (Breiding et al, 2015), is defined as the use of physical force with the potential for causing death, disability, injury, or harm. Family violence by patients with SMI is common in Japan and the US, with an estimated lifetime prevalence of 40% (Labrum and Solomon, 2015). Such violence is rarely studied because family violence is taboo and fears of further stigmatizing this population exist (Solomon et al, 2005).…”
Section: Family Violence By Patients With Smimentioning
confidence: 99%